2020
DOI: 10.1002/ange.201915833
|View full text |Cite
|
Sign up to set email alerts
|

Materialien mit Selektivität für oxidative Molekülspezies für die Diagnostik und Therapie

Abstract: Abbildung 1. A) Krankheiten, fürdie oxidativer Stress bedeutsam ist. B) Primäre Untergruppen oxidativer Molekülspezies, ihre Entstehungsund Transformationsreaktionen und ihre Halbwertszeit. a Die Halbwertszeit der verwandten Radikale hängt von den Umgebungsbedingungen ab. Caiyan Zhao ist als Postdoktorandin Stipendiatin an der Havard Medical School. Sie wurde 2018 in physikalischer Chemie am National Center for Nanoscience and Technology,C hinese Academy of Science (China) promoviert. Dann wechselte sie zur Fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 232 publications
(170 reference statements)
0
4
0
Order By: Relevance
“…Due to the short half-lives, high reactivity, and short diffusion distance of ClO – and other ROS, the quantitative detection of ClO – is still challenging by other established methods . Nevertheless, we believed that our in vivo ratiometric detection could potentially approach real data quantification based on in vitro investigation.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Due to the short half-lives, high reactivity, and short diffusion distance of ClO – and other ROS, the quantitative detection of ClO – is still challenging by other established methods . Nevertheless, we believed that our in vivo ratiometric detection could potentially approach real data quantification based on in vitro investigation.…”
Section: Resultsmentioning
confidence: 99%
“…Plotting ratiometric signals (F 808ex /F 980ex ) against ClO – concentration (0 to 16 μM) resulted in a strong linear correlation ( R 2 = 0.998, Figure e). Notably, the limit of detection (LOD) of this system was calculated to be 77 nM, which is much lower than the ClO – concentration in the physiological environment. , To further confirm the reliability of IR-808@DSNPs@DSPE-PEG-NH 2 for ratiometric imaging (detection) of ClO – , we examined these ratiometric signals under 1% intralipid with 1 mm depths and found that they could remain consistent without being affected by fluorescence attenuation (Figure S26). This result was in accordance with the result of Figure c, verifying the effectivity of IR-808@DSNPs@DSPE-PEG-NH 2 for ratiometric detection of ClO – in vivo .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations